Pengaruh Size, Current Ratio, Profabilitas, Activity dan Leverage Terhadap Cash Dividen pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Melani Melani; Seto Sulaksono Adi Wibowo (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
This study aims to determine whether there is influence between size, current ratio, profitability, activity and leverage against cash dividend on manufacturing companies listed in Indonesia Stock Exchange in 2010-2013. There are 135 companies that were observed, with purposive sampling technique then acquired 40 companies sampled. In this study, researchers used a classical assumption test, test hypotheses, and simple regression. the results of testing a simple hypothesis is there is one variable that significantly influence the cash dividend, the variable activity and four variables were not significant effect on the cash dividend, the size, current ratio, profitability, and leverage. Limitations of this study is a company that is used only manufacturing companies and the observation period was observed only four years. The implications and suggestions for further research are better add other variables that affect cash dividends, extend the period of observation, and his company type expanded again and should be using multiple regression test